Assessment of anaerobic endurance based on selected biochemical parameters in 400 m/400 m hurdles male athletes - Stolecka, A.; Kaczmarczyk, T.; Zebrowska, A. (Central European Journal of Sport Sciences and Medicine, 2016)
The ongoing development of the modern society may also be easily noticed in sports. Currently, to be able to compete at the highest level at major sporting events, it is essential to conduct scientific research to estimate the individual potential and skill level of an athlete. The aim of this study was to assess the anaerobic endurance in men competing in the running events of 400 m/400 m hurdles based on the estimation of maximum power, as well as selected biochemical and physiological parameters measured in a cardiac stress test at a supramaximal intensity. Seven athletes participated in the study and were subjected to a modified version of the Wingate test (Bar-Or, Dotan, Inbar, 1997; Bar-Or, Inbar, Skinder, 1996) which involved performing three runs of a 12-second endurance test on a cycloergometer at short intervals. This modification of the test allowed a more precise observation and a better understanding of the physiological and biochemical changes that decrease the efficiency as a result of repeated physical effort, which may significantly affect the assessment of the preparation of an athlete, and thus the assessment of the training process. The most significant changes in the course of the conducted study were observed in the values of the following biochemical parameters: glucose levels, acid-base balance of the blood and lactate levels.